A method for preparing a composite nerve conduit having an outer braided layer and an inner through-microchannel structure

By using the inner layer of the outer braided layer in the nerve catheter and combining the crosslinking technology of chitosan, gelatin and tea polyphenols, a directionally arranged through microchannel structure is formed, which solves the problem of insufficient mechanical performance in the repair of long-distance peripheral nerve damage, and achieves efficient nerve repair and antibacterial and antioxidant effects.

CN117258043BActive Publication Date: 2025-03-28SUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311225359.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-28
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

When repairing peripheral nerve damage at longer distances, existing nerve catheters have problems such as insufficient mechanical properties, difficult to control the channel aperture and difficult to form parallel arrangement of penetrating microchannels.

Method used

The composite nerve catheter preparation method is adopted to prepare a composite nerve catheter with the inner layer of the outer braided layer and the inner layer of the microchannel structure is formed by braiding polylactic acid yarn and forming a microchannel structure in the core. Combined with the cross-linking technology of chitosan, gelatin and tea polyphenols, a hydrogel with a through-microchannel structure with a directional arrangement is formed, and directional freezing is performed in a 3D printing mold.

Benefits of technology

It has achieved improvement in the mechanical properties of the nerve catheter, is suitable for cell proliferation and growth, has excellent antibacterial and antioxidant ability, can extend the distance for nerve defect repair, and reduce scar formation during the repair process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117258043B_ABST
    Figure CN117258043B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a composite nerve conduit with an outer braided layer and an inner through-microchannel structure, belonging to the field of nerve conduit material preparation. The internal gel filling liquid is cross-linked with polyethylene glycol dipropylene oxide ether to prolong the gelation time, which is convenient for simultaneous injection of large quantities of samples, and the internal microchannel sponge after freeze drying has good mechanical properties. In an in vitro lysozyme simulated in vivo degradation test, the composite nerve conduit prepared by the invention has a weight retention rate of more than 70% after 28 days of degradation, which can ensure that the conduit still retains a certain shape structure before the nerve is completely repaired after being implanted in the body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nerve conduit material preparation, and specifically relates to a method for preparing a composite nerve conduit with an outer braided layer and an inner through-microchannel structure. Background Art

[0002] There is a risk of peripheral nerve injury in sports, traffic accidents or construction accidents, and even iatrogenic peripheral nerve injury can occur during some surgical procedures. The degree of peripheral nerve damage can be divided into several different levels. Peripheral nerves with low damage levels have a certain degree of regeneration ability. When the distance of peripheral nerve injury is not long and there is no tension on the broken end, it can be sutured directly. After the distance of peripheral nerve injury exceeds a certain length, the method of tension-free nerve repair is subject to certain restrictions, and autologous nerve transplantation is considered to be the gold standard for treating peripheral nerve injury. However, this method also has certain defects, such as loss of sensory function, scarring and neuroma formation in the donor site. For patients with more peripheral nerve damage, there are problems such as limited donor nerve sources and mismatched nerve bundles. Artificial nerve conduits can solve this problem. In addition to avoiding secondary damage to autologous nerve transplantation and immune rejection of allogeneic nerve transplantation, artificial nerve conduits can also provide a repair channel for nerve regeneration, prevent fibroblasts and inflammatory cells from invading the repair channel, and reduce scar formation.

[0003] At present, most of the nerve conduits used in clinical practice are single-channel conduits. The hollow conduits have obvious disadvantages. The hollow structure may cause the regenerated axons to grow in an intertwined manner. In addition, the hollow tube lacks an internal support structure, and the regenerated axons are prone to shrinkage due to the hollow structure. Therefore, the hollow nerve conduits are only suitable for repairing shorter nerve injuries.

[0004] Studies have shown that through-microchannel catheters can greatly extend the distance of nerve defect repair. At present, the preparation methods of through-microchannel nerve catheters are electrospinning, molding, 3D printing, and weaving. However, the through-microchannel catheters prepared by the first three methods have a limited number of channels when preparing nerve catheters of the same diameter due to the thick inner channel wall, and the mechanical properties are biased. Although the weaving method has better mechanical properties, the number of channels is also limited, and the coarse fibers on the weaving surface are not conducive to cell adhesion and proliferation.

[0005] The use of ice crystal directional growth technology can overcome the difficulties of the above methods and produce dozens or even hundreds of channel structures. The nerve conduits with through-microchannel structures prepared by this method have a higher porosity, which is beneficial to the transport of nutrients and metabolites, and provides cells with sufficient adhesion area and growth space. Channels with appropriate pore sizes can avoid blockage of the channel due to swelling of the tube wall.

[0006] However, the through-microchannel nerve conduits prepared only by the ice crystal growth method also have problems such as poor mechanical properties and difficult to control the channel pore size. At present, some studies have also tried to use the ice crystal growth method to prepare through-microchannel conduits, but the channels formed are often too small in pore size, which is not conducive to cell growth, and the mechanical properties are limited.

[0007] At present, there is no research on generating a through-microchannel structure in a braided catheter. Generating a through-microchannel structure in a braided catheter has great technical difficulty. The present invention has found through repeated experiments that directional freezing under a certain temperature gradient requires lateral peripheral insulation, because the braided catheter has lateral pores, which easily form lateral internal channels, but cannot form longitudinal internal channels.

[0008] Therefore, the 3D printing mold specially designed and prepared by the present invention, combined with the outer wall coating treatment of the catheter, can solve this technical problem. Summary of the invention

[0009] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0010] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0011] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a composite nerve conduit having an outer braided layer and an inner through-microchannel structure.

[0012] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a composite nerve conduit having an outer braided layer and an inner through-microchannel structure, comprising:

[0013] S1: Using polylactic acid yarn as braiding yarn and polytetrafluoroethylene tube as core, braiding a catheter on a braiding machine, and braiding the braided catheter as core for secondary braiding to obtain a cored polylactic acid braided double-layer catheter;

[0014] S2: Prepare an acetic acid solution with a mass concentration of 1-2%, add chitosan at 55-65°C to fully dissolve, obtain a 2.2-2.8% w / v chitosan solution, add gelatin particles, and stir to obtain a mixed solution; add polyethylene glycol dipropylene oxide ether to the mixed solution under water bath conditions, the water bath temperature is 35-40°C, stir for 0.5-1h, then let it stand, continue cross-linking at room temperature for 10-12h, add 8-12% w / v tea polyphenols solution, stir evenly, remove bubbles, and obtain a braided catheter surface coating solution I;

[0015] S3: immersing the cored polylactic acid braided catheter into the braided catheter surface coating solution I, and then drying and repeating this step 1 to 2 times to obtain a pre-coated cored polylactic acid braided catheter;

[0016] S4: extracting the polytetrafluoroethylene tube from the pre-coated cored polylactic acid braided catheter, uniformly coating the braided catheter surface coating solution I on the surface of the braided tube, drying and then coating the tube 1 to 2 times to obtain a coated polylactic acid double-layer braided catheter;

[0017] S5: Prepare an acetic acid solution with a volume concentration of 2-3%, add chitosan at 55-65°C to fully dissolve, obtain a 3-4% w / v chitosan solution, add gelatin particles, and stir to obtain a mixed solution; add polyethylene glycol dipropylene oxide ether to the mixed solution under water bath conditions, the water bath temperature is 35-40°C, stir for 1-1.5 hours, then let it stand, continue cross-linking at room temperature for 12-16 hours, then add 8-12% w / v tea polyphenols solution, stir evenly, remove bubbles, and obtain braided catheter gel filling solution II;

[0018] S6: Inject the gel filling liquid II in the braided catheter into the coated polylactic acid double-layer braided catheter, put it into a 3D printed directional freezing mold, put the mold into a liquid nitrogen tank for 3 to 4 hours, take out the catheter, freeze-dry, neutralize, remove the acid and cross-linking agent, and prepare an antibacterial and antioxidant composite nerve catheter.

[0019] As a preferred embodiment of the preparation method of the present invention, the preparation method of the core-braided polylactic acid double-layer catheter comprises:

[0020] The catheter is braided on a 16-spindle or 24-spindle braiding machine using 50-80dtex polylactic acid yarn as braiding yarn and a polytetrafluoroethylene tube with a diameter of 2-4mm as a core, and then the braided catheter is used as a core for secondary braiding;

[0021] The core braided catheter is taken off the braiding machine, wrapped with aluminum foil, and heat-set for 20 to 50 minutes at a temperature of 145 to 160° C. to obtain a core polylactic acid braided double-layer catheter.

[0022] As a preferred embodiment of the preparation method of the present invention, in said steps S2 and S5, the mass ratio of chitosan to gelatin is 3-4:1, and the mass ratio of chitosan to gelatin in S2 and S5 is the same.

[0023] As a preferred embodiment of the preparation method of the present invention, wherein: in the steps S2 and S5, the mass ratio of chitosan to polyethylene glycol dipropylene oxide ether is 4-6:2, and the mass ratio of chitosan to polyethylene glycol dipropylene oxide ether in S2 and S5 is the same.

[0024] As a preferred embodiment of the preparation method of the present invention, in the steps S2 and S5, tea polyphenols account for 5-15% of the total mass of chitosan / gelatin / tea polyphenols, and the proportion of tea polyphenols in S2 and S5 is the same.

[0025] As a preferred embodiment of the preparation method described in the present invention, the mold includes a 3D printing mold area and a metal rod; the 3D printing mold area includes a nerve conduit placement area and a thermal insulation material area, the nerve conduit placement area is designed inside the thermal insulation material, and the metal rod is arranged below the nerve conduit placement area.

[0026] As a preferred solution of the preparation method of the present invention, the 3D printing mold has two grooves in its top view, the outer groove is the insulation material area, and the inner groove is the catheter placement area;

[0027] Among them, 15 to 30 small holes with a diameter of 1.5 to 2.5 mm are evenly arranged at the bottom of the inner groove, and a corresponding number of metal rods are inserted into the bottom of the small holes. At the same time, a corresponding number of braided catheters are placed in the mold as containers for placing the braided catheters. The gaps between the catheters are filled with easily deformable straws, and the outer groove is filled with high-density sponge as a thermal insulation material area.

[0028] As a preferred embodiment of the preparation method of the present invention, the neutralization, deacidification and cross-linking agent removal in step S6 comprises placing the catheter in a 0.05-0.2M Na2HPO4·12H2O solution, changing the water every 20-30 minutes, and after 2-3 hours, washing the catheter with deionized water to wash away the residual cross-linking agent; and performing secondary freeze drying using a freeze dryer.

[0029] Another object of the present invention is to overcome the shortcomings of the prior art and provide a composite nerve conduit with an outer woven layer and an inner through-microchannel structure prepared by a preparation method, wherein the composite nerve conduit comprises a double-layer woven outer conduit that has been subjected to multiple coating and cross-linking treatments, and the inner conduit is a hydrogel with a directionally arranged through-microchannel structure.

[0030] Beneficial effects of the present invention:

[0031] (1) The nerve conduit prepared by this method has an excellent internal structure suitable for cell proliferation and growth, and nerve repair and regeneration: it has a parallel through-microchannel structure with a pore size between 100-300 microns, which is suitable for cell growth.

[0032] (2) The microchannel sponge of the present invention is composed of chitosan, gelatin and tea polyphenols, and has good surface hydrophilicity, which is suitable for cell adhesion and growth; it has excellent antibacterial and antioxidant capabilities and can prevent the generation of inflammatory cells, neuromas, etc. in nerve repair.

[0033] (3) The internal gel filling liquid of the present invention is cross-linked with polyethylene glycol dipropylene oxide ether to prolong the gelation time, which is convenient for the simultaneous injection of large quantities of samples. The internal microchannel sponge after freeze-drying has excellent mechanical properties. In the in vitro lysozyme simulated in vivo degradation test, the weight retention rate is still more than 70% after 28 days of degradation, which can ensure that the catheter still retains a certain shape structure and mechanical properties before the nerve is completely repaired after implantation in the body, thus meeting the time requirements for nerve repair.

[0034] (4) The external PLA yarn braided structure of the present invention significantly improves the compressive strength and breaking strength of the catheter.

[0035] (5) The braided catheter of the present invention adopts a cross-linked coating of polyethylene glycol dipropylene oxide ether on the outside, so that the coating film has good mechanical properties and can maintain good flexibility, and has a low dissolution rate in a wet state, thereby solving the problem of easy disintegration of the braided tube and the problem of lateral heat conduction.

[0036] (6) The 3D printing mold in the present invention solves the technical problem of difficulty in forming parallel-arranged through microchannels in the braided tube. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0038] Figure 1 This is a schematic diagram of the directional freezing mold in Example 1 of the present invention.

[0039] Figure 2 Figure 3 is a morphological diagram of a braided coated catheter in an embodiment of the present invention, wherein the contents of tea polyphenols in the coating liquid of the four catheters from left to right in each small figure are 0%, 5%, 10%, and 15%, respectively; (a) is a diagram of a PEG-DE cross-linked braided coated catheter; (b) is a diagram of a PEG-DE cross-linked braided catheter 30 minutes after the solution was injected into the catheter.

[0040] Figure 3 The longitudinal and transverse SEM electron microscope images of the composite through-microchannel nerve conduit of the present invention in which the chitosan solution concentration of the gel filling liquid in the conduit under PEG-DE cross-linking is 3%, 4% and 5% respectively.

[0041] Figure 4 The longitudinal and transverse SEM electron microscope images of the composite through-microchannel nerve conduit in which tea polyphenols account for 0%, 5%, 10% and 15% of the total dry matter in the coating liquid or the gel filling liquid under PEG-DE cross-linking of the present invention.

[0042] Figure 5 It is a bar graph of the breaking strength and fracture intensity of the through-channel sponge inside the conduit and the entire composite through-channel nerve conduit of the present invention.

[0043] Figure 6 This is a diagram showing the effect of the composite through-microchannel nerve conduit of the present invention in scavenging DPPH free radicals.

[0044] Figure 7 This is a comparison chart of DPPH free radical scavenging rates of the composite through-microchannel nerve conduits with different tea polyphenol proportions of the present invention.

[0045] Figure 8 This is a test comparison diagram of Escherichia coli of the present invention.

[0046] Fig. 9 This is a test photograph of Staphylococcus aureus of the present invention.

[0047] Fig.10 This is a comparison chart of the weight retention rate of the microchannel sponge inside the catheter after degradation in lysozyme or PBS buffer.

[0048] Fig.11 This is a comparison chart of the CCK-8 absorbance values ​​of the composite nerve conduits with different proportions of tea polyphenols in the negative control, comparative example 1, example 4, example 1, and example 5 on rat Schwann cells.

[0049] Fig.12 The results of DAPI and FITC fluorescence staining can be used to observe the distribution of cells in the through-microchannel nerve conduit.

[0050] Fig.13 This is a comparison of the water contact angles of sponges with different proportions of tea polyphenols penetrating the microchannel. DETAILED DESCRIPTION

[0051] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0052] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0053] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0054] SEM observation of the braided coated catheter in the embodiment of the present invention:

[0055] The braided tube was cut longitudinally with scissors into a certain size, and then fixed on the sample stage with conductive glue, vacuum gold sprayed, and the surface structure of the braided tube was observed using an S-8100 scanning electron microscope.

[0056] Mechanical properties test of the braided coated catheter in the embodiment of the present invention:

[0057] Five groups of samples of braided tubes with each coating were selected, and the outer diameter of the braided tube was measured with a vernier caliper, and the radius value R (mm) was calculated; the tensile properties of the coated tube were tested using a fabric strength tester.

[0058] Set the pre-tension to 1N, the stretching speed to 10mm / min, the clamping length to 10mm, and stretch until the braided structure is destroyed. The calculation formula for the breaking strength of the braided coated catheter is as follows:

[0059]

[0060] Among them, (R 2 -1.5 2 )×π is the cross-sectional area of ​​the braided tube wall, and the stress-strain curve is drawn according to the breaking strength and breaking elongation.

[0061] For the compression test, the catheter was cut into 1 cm long pieces and fully moistened in PBS buffer. The compression resistance of the catheter was tested using a texture analyzer at a test speed of 10 mm / min and an initial stress of 0.02 N. The force corresponding to a strain of 50% was measured.

[0062] SEM observation of the sponge catheter with directional through-channels in the catheter in the embodiment of the present invention:

[0063] The composite through-microchannel nerve conduit was cut open in the transverse and longitudinal directions using a blade, and after vacuum gold spraying, the through-microchannel structure of the composite through-microchannel nerve conduit was observed under an S-4800 scanning electron microscope.

[0064] Porosity test of the directional through-microchannel sponge in the catheter in the embodiment of the present invention:

[0065] The porosity of the through-microchannel sponges prepared by two cross-linking methods was tested using the ethanol replacement method.

[0066] The dried through-microchannel sponge was cut into 3 cm lengths, 3 parallel samples were taken from each group of catheters, and the dry weight Ws of the catheters was recorded.

[0067] Place the catheter in anhydrous ethanol and apply negative pressure for 30 minutes until no bubbles overflow from the catheter surface. Weigh and record the weight as W1. Take out the catheter and weigh the anhydrous ethanol again, record it as W2. The calculation formula for the porosity P of the catheter is as follows:

[0068] The present invention composite Mechanical properties test of through-microchannel nerve conduit:

[0069] The composite through-microchannel catheter at 4% chitosan concentration in the PEG-DE cross-linking group was tested, and the outer diameter of the catheter was measured using a vernier caliper, and the radius value R, mm, was calculated;

[0070] According to the calculation of porosity, the actual area of ​​the through-microchannel sponge is measured to be (1-P)×1.52×π. The breaking strength calculation formula of the composite through-microchannel nerve conduit is as follows:

[0071]

[0072] Among them, (R 2 -1.5 2 )×π+(1-P)×1.5 2 ×π is the area of ​​the braided tube wall plus the through-microchannel sponge.

[0073] Contact angle testing method in the embodiment of the present invention:

[0074] The static contact angle of the surface of the through-microchannel sponge was tested using an OCA 30 video screen optical contact angle meter. The through-microchannel sponge was cut longitudinally, cut into fixed sizes using scissors, placed on a glass slide, and placed on the contact angle measurement table. The position of the measurement platform and the size of the light source were adjusted, and the focal length was adjusted to ensure image clarity.

[0075] Turn the syringe knob to slowly drip deionized water onto the sample surface, and use the software to quickly capture the contact angle image. Repeat the measurement three times for each group of samples, and use the software to measure the contact angle.

[0076] Degradation performance test of the directional through-channel sponge in the catheter of the present invention:

[0077] The degradation performance of the through-microchannel sponge at 4% chitosan concentration in the PEG-DE cross-linking group and the through-microchannel sponge at 2.5% glutaraldehyde dosage in the CA / GA composite cross-linking group in lysozyme or PBS buffer was tested. Lysozyme was dissolved in PBS buffer to obtain a lysozyme solution with a concentration of 2 mg / mL. Weigh a certain weight of catheter, recorded as Wi, completely immersed in the solution, placed in a 37°C constant temperature water bath oscillating box, and the degradation solution was replaced every 7 days. After 3d, 7d, 12d, 19d, and 28d, the catheter was removed from the solution, rinsed with deionized water, dried and weighed, recorded as Wt. The weight retention rate of the catheter after degradation can be calculated according to the following formula:

[0078]

[0079] DPPH free radical scavenging performance in the embodiment of the present invention:

[0080] Take 9.86 mg of DPPH powder and dissolve it in anhydrous ethanol, dilute to 100 mL, and obtain a DPPH solution with a concentration of 0.25 mM. Cut the composite through-microchannel nerve conduits with different proportions of tea polyphenols into 2 cm long sizes and oscillate at a constant temperature of 37°C in PBS buffer for 24 hours. Take 1.5 mL of sustained-release solution, add 1.5 mL of DPPH ethanol solution and mix evenly, and place in a dark environment for 30 minutes. Measure the absorbance at an ultraviolet wavelength of 517 nm, and the value is recorded as As. Take 1.5 mL of PBS solution instead of the sample sustained-release solution, add 1.5 mL of DPPH solution, mix evenly, and measure the absorbance at 517 nm, which is recorded as Ab. Set up 3 parallel samples for each sample, take the average absorbance, and calculate the free radical scavenging rate according to the formula:

[0081]

[0082] Rat Schwann cell culture in the present invention:

[0083] Preparation of complete culture medium: In an ultra-clean workbench, prepare complete culture medium in the ratio of high glucose culture medium: special grade fetal bovine serum: double antibody (penicillin / streptomycin solution) = 89:10:1, and mix with a pipette to avoid bubbles.

[0084] Cell recovery: Take out the cryotube from the liquid nitrogen tank, quickly put it into a 37℃ water bath and gently rotate it. After the cell suspension is completely thawed, disinfect it with alcohol and send it into the biosafety cabinet. Use a pipette to aspirate the recovered cells into a 15mL centrifuge tube, add a certain amount of complete culture medium to dilute it, and centrifuge it in a centrifuge at 900r / min for 5min.

[0085] Cell culture: Pour off the supernatant, add a certain amount of complete culture medium to resuspend the cells, and finally transfer the cell suspension to a T75 cell culture flask for culture.

[0086] Cell passaging:

[0087] Observe the cell growth under an inverted fluorescence microscope. When the cell growth confluence reaches more than 85%, the cells can be subcultured. Remove the complete medium from the culture bottle, add a certain amount of trypsin to digest the cells, and place them in a cell culture incubator for 3 minutes. After the cell digestion is completed, add a certain amount of complete medium and gently blow. Aspirate the cell suspension into a 15mL centrifuge tube and centrifuge at 900r / min for 5 minutes. Pour off the supernatant and resuspend the cells. Aspirate 10μL of the suspension for cell counting.

[0088] Cell seeding:

[0089] Before cell inoculation, the dried 1 cm long composite through-microchannel nerve conduit was cut longitudinally and placed in a glass bottle, sterilized in a high temperature and high pressure sterilizer for half an hour, rinsed with D-PBS 3 times, and finally dried with sterilized filter paper. The conduit was spread flat in a 24-well plate and irradiated with ultraviolet light for 30 minutes. 40 μL of cell suspension was inoculated into the longitudinal section of the conduit, and 8×104 cells were inoculated in each well. The cell culture plate was placed in a carbon dioxide incubator for 30 minutes. After the cells adhered to the wall, 0.5 mL of complete culture medium was added to each well, and the culture medium was replaced every two days.

[0090] Cryopreservation of cells:

[0091] Complete medium was added to the cell suspension after centrifugation to dilute the cell concentration to 2×106 cells / mL. A certain amount of DMSO was added to prevent ice crystals from damaging the cells. The cells were divided into cryopreservation tubes and numbered. The cryopreservation tubes were placed in a gradient cooling box and frozen in a -80℃ refrigerator for 24 hours. The gradient cooling box was taken out and the cryopreservation tubes were placed in liquid nitrogen for long-term storage.

[0092] CCK-8 cell proliferation test:

[0093] CCK-8 can be reduced to a water-soluble orange-yellow formazan product by dehydrogenases in mitochondria. The activity of the cell sample to be tested can be detected by measuring the absorbance value of the cell fluid with an enzyme-labeled instrument. Take out the cell culture plates after 1, 3, 5, and 7 days of culture from the incubator, disinfect them and send them to the operating table. Aspirate the waste liquid in the culture plate and clamp the catheter into a new cell culture plate. Prepare a 10% CCK-8 solution under light-proof conditions. Add 500 μL of CCK-8 solution to each well. Wrap it with aluminum foil and shake it gently for 10 minutes. Place it in the incubator and react for 3 hours. Take 100 μL from each well and aspirate it into a 96-well plate, and use an enzyme-labeled instrument to detect the absorbance value at 450nm.

[0094] SEM cell morphology observation:

[0095] Fix the cell-ducts on the 5th and 7th day of culture. First, aspirate the liquid in the 24-well plate and rinse with PBS twice, 10 minutes each time. Take 0.5mL of 2.5% (v / v) glutaraldehyde solution to fix the cells on the duct. Let it stand at 4°C for 4 hours. Then aspirate the solution and wash it with PBS buffer twice, 10 minutes each time. Dehydrate the cells step by step with 30%, 50%, 70%, 90%, and 100% ethanol solutions by volume, 10 minutes each time. Dry at room temperature after dehydration. Observe the growth of cells in the longitudinal section of the duct under a scanning electron microscope.

[0096] Observation of cell-complex through-microchannel nerve conduit staining:

[0097] Take the cell culture plates on the 5th and 7th day of culture, discard the complete culture medium, and rinse the cells 3 times with PBS buffer for 5 minutes each time. Use 2.5% glutaraldehyde solution to fix the cells for 10 minutes, and rinse them 3 times with PBS buffer for 5 minutes each time. Prepare 0.5% Triton-X100 permeabilization solution, use the permeabilization solution to permeabilize the cells for 5 minutes, and rinse them 3 times with PBS buffer for 5 minutes each time. Protect from light and prepare 1‰ DAPI solution. Add a certain amount of DAPI staining solution to each well to ensure that the composite through-microchannel nerve conduit is completely immersed in the staining solution, stain for 5 minutes, and rinse 3 times with PBS buffer. Use a confocal microscope to observe cell growth.

[0098] Weigh a certain amount of FITC powder and dissolve it in DMSO to prepare a FITC solution with a concentration of 1 mg / mL. Use PBS buffer to dilute to 10 μg / mL. Take a certain amount of FITC staining solution and add it to the composite through-microchannel nerve conduit stained with DAPI to ensure that the staining solution is completely immersed. Stain for 5 minutes and rinse with PBS buffer 3 times. Use a confocal microscope to observe cell growth.

[0099] Example 1

[0100] This example provides the preparation of a composite conduit with a through microchannel structure at a concentration of 10% tea polyphenols + 4% chitosan:

[0101] Step 1: 3D Printing of Directed Freezing Molds

[0102] Use 3D modeling software to design the directional freezing mold and create a 3D printing model.

[0103] The designed model was printed on an industrial 3D printer using 2mm diameter PLA printing filament.

[0104] After printing, the mold is combined with a metal rod of a certain length to form a Figure 1The mold shown on the left side includes a 3D printing mold area and a metal rod; wherein the 3D printing mold area includes a nerve conduit placement area and a thermal insulation material area, the nerve conduit placement area is arranged inside the thermal insulation material, and the metal rod is arranged below the nerve conduit placement area;

[0105] The 3D printing mold has two grooves in its top view, the outer groove is the insulation material area, and the inner groove is the catheter placement area; wherein, 15 to 30 small holes with a diameter of 1.5 to 2.5 mm are evenly arranged at the bottom of the inner groove, a corresponding number of metal rods are inserted into the bottom of the small holes, and a corresponding number of braided catheters are placed in the mold at the same time as a container for placing the braided catheters, and the gaps between the catheters are filled with easily deformable straws, and the outer groove is filled with high-density sponge as the insulation material area;

[0106] Place the mold in a liquid nitrogen tank to form a directional freezing device, such as Figure 1 Shown on the right.

[0107] Step 2: Preparation of polylactic acid braided catheter

[0108] (1) Using polylactic acid yarn, double-layer braiding is performed on a 16-spindle braiding machine, and a polytetrafluoroethylene tube with a diameter of 3 mm is used as the core yarn for braiding.

[0109] (2) The braided catheter with a core is removed from the braiding machine, wrapped with aluminum foil, and then heat-set at 145° C. for 30 minutes.

[0110] Step 3: Coating of PLA braided catheter

[0111] (1) Preparation of coating solution: Prepare acetic acid solution with a mass concentration of 1.5%, add a certain amount of chitosan, and fully dissolve it at 60°C to obtain a 2.5% (w / v) chitosan (CS) solution; then add a certain amount of gelatin (GE) particles, wherein the mass ratio of chitosan to gelatin is 4:1, and stir thoroughly;

[0112] Add the crosslinking agent polyethylene glycol dipropylene oxide ether (PEG-DG) to the mixed solution, add it to the CS / GE mixed solution at a mass ratio of chitosan: PEG-DE = 2:1, and let it stand for crosslinking at room temperature for 12 hours;

[0113] A certain amount of 10% (w / v) tea polyphenol solution was added and stirred thoroughly to make the tea polyphenol account for 10% of the total mass of chitosan / gelatin / tea polyphenol.

[0114] (2) Front coating: Immerse the cored catheter in the coating solution for 10 minutes, dry it, and repeat this step once.

[0115] (3) Post-coating: Pull out the polytetrafluoroethylene tube, evenly apply the coating solution on the surface of the braided tube, dry it and then apply the coating again.

[0116] Step 4: Preparation of gel filling liquid in braided tube

[0117] (1) Chitosan / gelatin solution: prepare chitosan acetate solution with a mass concentration of 4%;

[0118] A certain amount of gelatin particles was added to the prepared chitosan solution to fully dissolve it, wherein the mass ratio of chitosan to gelatin was 4:1.

[0119] (2) In a 37°C water bath, the crosslinking agent PEG-DG was added to the chitosan / gelatin mixed solution at a ratio of chitosan:PEG-DE=5:2, and crosslinked at room temperature for 12 h.

[0120] (3) Take a certain amount of 10% (w / v) tea polyphenol solution, add it to the above solution and stir evenly so that tea polyphenol accounts for 10% of the total mass of chitosan / gelatin / tea polyphenol, and remove bubbles by ultrasound.

[0121] Step 5: Generation of microchannel sponge in the catheter

[0122] (1) Use a syringe to inject the gel filling liquid into the braided tube after the third step coating reinforcement.

[0123] (2) Bundle the braided tubes together and place them into the 3D printed mold in step 1. Then place the mold into a liquid nitrogen tank for 3 hours. Control the height of the mold so that the metal rod at the bottom of the mold is always in contact with the liquid nitrogen surface.

[0124] (3) Remove the group of catheters from the mold and place them in a freeze dryer for lyophilization for 24 hours.

[0125] (4) Use 0.1M Na2HPO4·12H2O to neutralize the acetic acid in the catheter, then wash the catheter with deionized water to wash away the residual cross-linking agent. Then perform a second freezing and dry it again using a freeze dryer.

[0126] (5) The dried catheter is sealed and stored in a vacuum chamber away from light.

[0127] Example 2

[0128] Preparation of composite catheter with through-microchannel structure at a concentration of 10% tea polyphenols + 3% chitosan:

[0129] Based on Example 1, only the chitosan concentration in the chitosan / gelatin solution in part (1) of step 4 was changed to 3%.

[0130] Example 3

[0131] Preparation of composite catheter with through-microchannel structure at a concentration of 10% tea polyphenols + 5% chitosan:

[0132] Based on Example 1, only the chitosan concentration in the chitosan / gelatin solution in part (1) of step 4 was changed to 5%.

[0133] Example 4

[0134] Preparation of composite catheter with through-microchannel structure at a concentration of 5% tea polyphenols + 4% chitosan:

[0135] Based on Example 1, only the amount of tea polyphenol added in step 3 and step 4 was changed, and the tea polyphenol in the outer catheter outer wall coating liquid and the catheter gel filling liquid accounted for 5% of the total mass of chitosan / gelatin / tea polyphenol.

[0136] Example 5

[0137] Preparation of composite catheter with through-microchannel structure at a concentration of 15% tea polyphenols + 4% chitosan:

[0138] Based on Example 1, only the amount of tea polyphenol added in step 3 and step 4 was changed, and the tea polyphenol in the outer catheter outer wall coating liquid and the catheter gel filling liquid accounted for 15% of the total mass of chitosan / gelatin / tea polyphenol.

[0139] Comparative Example 1

[0140] Preparation of composite catheter with through-microchannel structure at 0% tea polyphenols + 4% chitosan concentration:

[0141] On the basis of Example 1, only the amount of tea polyphenol added in step 3 and step 4 was changed, and tea polyphenol was not added to the outer wall coating liquid of the outer catheter and the gel filling liquid in the catheter.

[0142] Result analysis:

[0143] (1) Catheter surface morphology after catheter coating and leakage after gel injection:

[0144] The catheter needs to withstand a certain amount of suture force when implanted in the body, and coating can further improve the stability of the braided structure. If the braided catheter is not coated, it is difficult for the braided structure to meet the standard of use in terms of strength, and the soft braided yarn may easily damage the braided structure, such as: the catheter is flattened, the middle section is loose, and the two ends are loose, so the yarn needs to be coated to obtain a braided catheter with a stable size.

[0145] In the present invention, the solution needs to be injected into the braided tube, and the gaps between the interwoven braided yarns will cause the solution to leak out, and the gaps in the tube wall will cause cold air to enter the tube from the pores on the side wall of the tube, which may make the lateral temperature transfer rate much greater than the longitudinal temperature transfer rate, resulting in a transverse channel. Coating the braided tube can solve this problem.

[0146] Figure 2 The four catheters in (a) are braided coated catheters when the tea polyphenol content in the coating liquid is 0%, 5%, 10%, and 15% from left to right, corresponding to the catheters in Comparative Example 1, Example 4, Example 1, and Example 5. It can also be seen from the figure that as the proportion of tea polyphenol increases, the color gradually deepens (from left to right). The coated catheters are uniform in thickness and can be cut into a certain length according to the requirements of nerve repair.

[0147] Because the catheter needs to be immediately placed in a 3D mold for gradient freezing after being injected into the gel solution, the catheter needs to be placed vertically during the process of being placed in the mold so that its temperature gradient direction is from bottom to top. Therefore, the solution injected into the catheter needs to have a certain viscosity so that it is not easy to flow out of one end of the catheter or leak sideways. Therefore, a cross-linking agent needs to be added to increase its viscosity and partially gel. Therefore, after adding the cross-linking agent PEG-DG, the gel time of the solution is extended, which is not only easy to operate, but also does not affect the formation of directional channels in the gel.

[0148] Figure 2 (b) is a photograph of the braided coated tubes in Comparative Example 1, Example 4, Example 1 and Example 5 after being injected with chitosan / gelatin / tea polyphenol gel solution and left to stand for 30 minutes. From the figure, it can be seen that the four tubes did not leak within 30 minutes of injection of the solution, and the tubes did not show obvious softening and deformation.

[0149] (2) Internal structure of the composite conduit with a through-microchannel structure

[0150] Figure 3 The longitudinal and transverse SEM electron microscope images of the composite through-microchannel nerve conduits with PEG-DE cross-linked conduits having chitosan solution concentrations of 3%, 4%, and 5% (Example 2, Example 1, and Example 3, respectively).

[0151] It can be seen from the figure that all directional through-microchannel sponges have an ideal directional through-microchannel structure. When the chitosan concentration is 3%, the pore sizes of the through-microchannels are different, the average pore size is greater than 400μm, and the number of channels is small. When the concentration is 4%, the pores on the cross section of the catheter are narrow and long, and are arranged in an orderly layered manner, with a pore size of about 200μm. As the concentration increases further, the catheter channel is irregularly circular, but the pore size becomes significantly smaller, less than 100μm. In addition, the increase in viscosity and the decrease in water content of the 5% chitosan solution lead to an increase in the viscous resistance to ice crystal growth, which may cause the directional channel structure to be destroyed. In the repair of peripheral nerve injury, the channel pore size of the through-microchannel nerve catheter is a key factor affecting its performance, and is crucial to cell adhesion, proliferation, and migration. Studies have shown that a pore size of about 200μm is an ideal pore size for repairing axon regeneration.

[0152] Therefore, a relatively ideal parallel-arranged through-microchannel structure can be obtained by selecting a chitosan concentration of 4%.

[0153] Figure 4 The longitudinal and transverse SEM electron microscope images of the composite through-microchannel nerve conduit with tea polyphenols accounting for 0%, 5%, 10%, and 15% of the total dry matter in the coating liquid or the gel filling liquid under PEG-DE cross-linking (Comparative Example 1 and Example 4, Example 1 and Example 5, respectively), among which, (A) PEG-DE / TPP-0%, (B) PEG-DE / TPP-5%, (C) PEG-DE / TPP-10%, and (D) PEG-DE / TPP-15%.

[0154] It can be seen that with the increase in the proportion of tea polyphenols, the aspect ratio of the pore size of the through-microchannel conduit begins to increase, and the shape of the pore changes from an irregular circle to a narrow and long shape. The maximum pore size can reach 300μm. Each concentration of tea polyphenols can obtain a relatively ideal parallel-arranged through-microchannel structure.

[0155] (3) Determination of the hydrophilicity of the composite catheter with a through-microchannel structure

[0156] The results of the measurement can be found in Fig.13 Among them, (A) PEG-DE / TPP-0%, (B) PEG-DE / TPP-5%, (C) PEG-DE / TPP-10%, and (D) PEG-DE / TPP-15%, respectively, are Comparative Example 1, Example 4, Example 1, and Example 5. The hydrophilicity pictures of the sponge inside the catheter show that the water contact angles of the sponges with internal through-microchannel structures in all examples are less than 90°.

[0157] Chitosan, gelatin, and tea polyphenols are all materials with good hydrophilic properties. In theory, the through-microchannel sponge containing these three materials should have excellent hydrophilic properties. However, due to the use of the crosslinker PEG-DE, which has an epoxy group at each end, it undergoes a ring-opening addition reaction with the amino group in chitosan or gelatin under mild room temperature conditions and connects to the through-microchannel sponge to form a structure with the methylene facing outward, resulting in enhanced hydrophobicity of the material and a larger contact angle.

[0158] from Fig.13 It can be seen that as the proportion of tea polyphenols in the material increases, the water contact angle of the through-microchannel sponge gradually decreases, and the hydrophilicity of the through-microchannel sponge gradually improves. This is mainly because the free hydroxyl groups of tea polyphenols combine with water to enhance the hydrophilicity of the membrane surface. When the content of tea polyphenols is 15%, the water contact angle is the smallest, at 41.1°±4.2°, which is conducive to the adhesion and growth of cells.

[0159] (4) Mechanical properties of composite catheters with through-microchannel structures

[0160] After peripheral nerve damage is repaired, the body's activities will stretch and squeeze the repaired area, so the nerve conduit's resistance to stretching is crucial.

[0161] The breaking performance of the composite through-microchannel nerve conduit in the present invention is determined by the maximum tensile force borne when the braided structure is destroyed.

[0162] Figure 5 The figure is a bar graph of the breaking strength and fracture strength of the through-microchannel sponge inside the catheter and the entire composite through-microchannel nerve catheter. Figure 5 (A) It can be seen that the breaking strength of the through-microchannel sponge without tea polyphenols is 15.68N, and its breaking strength gradually decreases with the increase of tea polyphenols. When the through-microchannel sponge is combined with the polylactic acid braided tube, the breaking strength of the composite through-microchannel nerve conduit is significantly increased, and the influence of the change of tea polyphenols content on the breaking strength of the composite conduit is relatively reduced. Figure 5(B) is the breaking strength of the through-microchannel sponge and the composite through-microchannel nerve conduit. The breaking strength of the through-microchannel sponge without tea polyphenols is greater than that of the composite through-microchannel nerve conduit. As the proportion of tea polyphenols increases, the breaking strength of the through-microchannel sponge gradually decreases. However, for the composite through-microchannel nerve conduit, the breaking strength of the composite through-microchannel nerve conduit without tea polyphenols is 17.57MPa, and the breaking strength of the composite through-microchannel nerve conduit with a tea polyphenol content of 15% is 14.34MPa. It can be seen that the change in tea polyphenol content has little effect on its breaking strength. Rydevik et al. [Rydevik BL, Kwan Michael K, Myers Robert R. An in vitro mechanical and histological study of acute stretching on rabbit tibial nerve [J]. Journal of Orthopaedic Research. 1990 (8): 694-701.] tested that the rabbit tibial nerve can withstand a maximum breaking strength of 11.7MPa. The composite through-microchannel artificial nerve conduit prepared in this study has good mechanical properties.

[0163] (5) Antioxidant properties of composite conduits with through-microchannel structures

[0164] DPPH free radical appears purple in ethanol solution. Figure 6 As shown, (A) DPPH free radical solution diagram, (B) PEG-DE / TPP-0% group catheter scavenging DPPH free radical effect diagram, (C) PEG-DE / TPP-5% group catheter scavenging DPPH free radical effect diagram, (D) PEG-DE / TPP-10% group catheter scavenging DPPH free radical effect diagram, (E) PEG-DE / TPP-15% group catheter scavenging DPPH free radical effect diagram.

[0165] The antioxidant activity of tea polyphenols comes from the fact that there are multiple phenolic hydroxyl groups on the benzene ring, which can provide an electron to the free radical and reduce the DPPH free radical to yellow diphenyl picrylhydrazine, such as Figure 6 As shown in (C) to (E).

[0166] As the proportion of tea polyphenols increases, the release of tea polyphenols increases, and the free radical scavenging effect becomes better. Figure 7 shown.

[0167] The DPPH free radical scavenging rate of the nerve conduit without tea polyphenols is 0, and the color of the free radical solution does not change significantly, such as Figure 6As shown in (B), the free radical scavenging rate increased with the increase of tea polyphenols, and the DPPH free radical scavenging rate of the catheter with 15% tea polyphenols could reach 70.9%.

[0168] (6) Antibacterial properties of composite catheters with through-microchannel structures

[0169] According to GB / T 20944.3-2008 “Evaluation of antibacterial properties of textiles”, the antibacterial properties of composite through-microchannel nerve conduits with different proportions of tea polyphenols were determined by the AQUA oscillation method.

[0170] Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 25923) were selected as bacterial species for evaluating the antibacterial properties of the composite through-microchannel nerve conduit, and PBS was selected as the negative control group, Comparative Example 1 was the blank control, and Example 4, Example 1 and Example 5 were three experimental groups.

[0171] Figure 8 These are test photos of Escherichia coli, and (AE) are negative control; 0%; 5%; 10%; 15% tea polyphenols ratio. Fig. 9 These are test photos of Staphylococcus aureus, (AE) are negative control; 0%; 5%; 10%; 15% tea polyphenols ratio.

[0172] Depend on Figure 8 and Fig. 9 It can be seen that the antibacterial effect of the composite through-microchannel nerve conduit without tea polyphenols on Escherichia coli and Staphylococcus aureus is poor, with the inhibition rates being 52.42% and 49.73%, respectively. When the proportion of tea polyphenols is 5%, the inhibition rates on Escherichia coli and Staphylococcus aureus are 70.9% and 81.67%, respectively, and the inhibition rates are both above 70%, which has a certain antibacterial effect. When the proportion of tea polyphenols is 10%, the inhibition rates of the composite through-microchannel nerve conduit on Escherichia coli and Staphylococcus aureus are 76.81±2.1% and 96.85±1.2%, respectively, and it has an excellent antibacterial effect on Staphylococcus aureus. With the increase of the proportion of tea polyphenols, the more tea polyphenols are released in the composite through-microchannel nerve conduit, the better the antibacterial effect. The antibacterial rates of the composite through-microchannel nerve conduit with 15% tea polyphenols against Escherichia coli and Staphylococcus aureus were 93.93±1.4% and 99.47±1.6%, respectively, exceeding 90% and 99% respectively. Tea polyphenols have a better antibacterial effect on Staphylococcus aureus, because the hydrophilic tea polyphenols can easily enter the cells through the proteins on Staphylococcus aureus to exert antibacterial effects.

[0173] (7) Degradation performance of the internal sponge with a through-microchannel structure

[0174] Fig.10 It is the weight retention rate of the sponge with through-microchannels inside the catheter after degradation in lysozyme or PBS buffer. There are 4 samples in total in the figure, namely Comparative Example 1 and Example 4. In Example 1 and Example 5, the internal sponge with a through-microchannel structure inside the catheter has the addition amount of tea polyphenols of 0%, 5%, 10% and 15%, respectively.

[0175] The degradation rate of the PEG-DE / TPP-10% group of through-microchannel sponges degraded by PBS buffer was very low. When the degradation time reached 28 days, the weight retention rate of the catheter could be maintained at about 89.37%. All through-microchannel sponges showed a rapid decrease in weight on the third day, which may be due to the fact that chitosan is a highly degradable biomaterial and the free chitosan molecules that were not cross-linked in the through-microchannel wall were decomposed by lysozyme. On the 3rd and 18th days, the weight loss of the through-microchannel sponges in the PEG-DE / TPP-15% group was higher than that of the other groups, mainly because the catheter contained more tea polyphenols, which were released from the catheter during the degradation process. On the 18th and 28th days, the degradation rate slowed down. The weight loss rate of the nerve conduit without tea polyphenols was less than that of the nerve conduits in other groups at the 12th day and later time points, and the weight retention rate on the 28th day was 84.43%, indicating that the nerve conduit cross-linked by PEG-DE has excellent anti-degradation ability. The weight retention rates of the through-microchannel sponges with tea polyphenols accounting for 5%, 10% and 15% were 77.67%, 79.84% and 79.31%, respectively, indicating that the addition of tea polyphenols has a certain effect on the degradation performance of the through-microchannel sponges.

[0176] (8) Evaluation of the cytocompatibility of composite catheters with through-microchannel structures

[0177] Rat Schwann cells were cultured on the cross section of the catheter, and the adhesion and proliferation of the cells on the scaffold were observed.

[0178] Fig.11 These are the CCK-8 absorbance values ​​of the composite nerve conduits with different proportions of tea polyphenols in negative control, comparative example 1, example 4, example 1 and example 5 on rat Schwann cells.

[0179] from Fig.11It can be seen that in all types of composite catheters, rat Schwann cells can achieve sustained proliferation, indicating that all test samples are non-cytotoxic. In all culture times, the proliferation capacity of catheter cells without tea polyphenols is the greatest, and the absorbance value on the 7th day of culture is the highest. In the first 3 days of culture, with the increase of tea polyphenols content, the cell proliferation performance is good, which may be that the protrusions in the through-microchannel wall are conducive to cell adhesion. With the extension of culture time, the cell proliferation ability decreases with the increase of tea polyphenols. Chitosan and gelatin are both natural polymer materials with biocompatibility, especially gelatin's low antigenicity and arginine-glycine-aspartic acid sequence, which is more conducive to cell proliferation. Tea polyphenols have excellent antibacterial, anti-inflammatory and free radical scavenging effects. The cell proliferation performance of composite through-microchannel nerve catheters with too much tea polyphenols is slightly worse than that of catheters with less tea polyphenols or without tea polyphenols. It may be due to the large proportion of tea polyphenols, resulting in a relatively high amount of tea polyphenols released into the culture medium, which makes the drug concentration in the culture medium too high, but affects cell proliferation. However, each group of samples still maintained a high proliferation rate until the 7th day, indicating that although the cell proliferation rate decreased with the increase in the amount of tea polyphenols added, no obvious cytotoxicity was produced.

[0180] The results of DAPI and FITC fluorescence staining can be used to observe the distribution of cells in the microchannel nerve conduit. Fig.12 . Fig.12 (A)-(D) are fluorescence confocal photos of rat Schwann cells adhering and growing on the composite nerve conduits in Comparative Example 1, Example 4, Example 1, and Example 5, respectively. From the DAPI staining fluorescence photos on the 7th day in the figure, it can be seen that a large number of cells can also be seen in the through microchannels with tea polyphenol content of 10% and 15%, and there is no significant difference in the number of cells in the channel without tea polyphenols. It can be observed that the number of cells is large and has been connected in groups. It can be clearly seen that the cells migrate and grow in a directional manner along the channel wall, indicating that on the one hand, the aperture size of the through microchannel is just suitable for the large-scale proliferation and growth of cells, and on the other hand, the directional through microchannel structure is conducive to guiding the directional migration and growth of cells. After implantation in the body, it is conducive to the migration and convergence of nerve stump cells and growth factors from both ends to the middle along the inner wall of the channel, accelerating the speed of nerve regeneration and repair, and extending the length of nerve repair.

[0181] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a composite nerve conduit having an outer braided layer and an inner through-microchannel structure, characterized in that: include, S1: Using polylactic acid yarn as braiding yarn and polytetrafluoroethylene tube as core, braiding a catheter on a braiding machine, and using the braided catheter as core for secondary braiding to obtain a cored polylactic acid braided double-layer catheter; S2: Prepare acetic acid solution with a mass concentration of 1-2%, add chitosan and fully dissolve it at 55-65°C to obtain 2.2-2.8% w / v chitosan solution, add gelatin particles, and stir to obtain a mixed solution; add polyethylene glycol dipropylene oxide ether to the mixed solution under water bath conditions, the water bath temperature is 35-40°C, stir for 0.5-1h, then let it stand, continue cross-linking at room temperature for 10-12h, add 8-12% w / v tea polyphenol solution, stir evenly, remove bubbles, and obtain braided catheter surface coating solution I; S3: immersing the cored polylactic acid braided catheter into the braided catheter surface coating solution I, and then drying and repeating this step 1-2 times to obtain a pre-coated cored polylactic acid braided catheter; S4: extracting the polytetrafluoroethylene tube from the pre-coated cored polylactic acid braided catheter, uniformly coating the braided catheter surface coating solution I on the surface of the braided tube, drying and then coating the tube 1-2 times to obtain a coated polylactic acid double-layer braided catheter; S5: Prepare acetic acid solution with a volume concentration of 2-3%, add chitosan and fully dissolve it at 55-65℃ to obtain 3-4% w / v chitosan solution, add gelatin particles, and stir to obtain a mixed solution; add polyethylene glycol dipropylene oxide ether to the mixed solution under water bath conditions, the water bath temperature is 35-40℃, stir for 1-1.5 h, then let it stand, continue cross-linking at room temperature for 12-16 h, then add 8-12% w / v tea polyphenol solution, stir evenly, remove bubbles, and obtain braided catheter gel filling solution II; S6: injecting the gel filling liquid II in the braided catheter into the coated polylactic acid double-layer braided catheter, placing it into a 3D printed directional freezing mold, placing the mold into a liquid nitrogen tank for 3-4 hours, taking out the catheter, freeze-drying, neutralizing, removing acid and cross-linking agent, and preparing an antibacterial and antioxidant composite nerve catheter; The mold includes a 3D printing mold area and a metal rod; wherein the 3D printing mold area includes a nerve catheter placement area and a thermal insulation material area, the nerve catheter placement area is arranged inside the thermal insulation material, and the metal rod is arranged below the nerve catheter placement area; The 3D printing mold has two grooves in its top view, the outer groove is the insulation material area, and the inner groove is the catheter placement area; wherein, 15 to 30 small holes with a diameter of 1.5 to 2.5 mm are evenly arranged at the bottom of the inner groove, and a corresponding number of metal rods are inserted into the bottom of the small holes. A corresponding number of braided catheters are also placed in the mold as containers for placing the braided catheters. The gaps between the catheters are filled with easily deformable straws, and the outer groove is filled with high-density sponge as the insulation material area.

2. The preparation method according to claim 1, characterized in that: The preparation method of the core-carrying polylactic acid braided double-layer catheter comprises: The catheter is braided on a 16-spindle or 24-spindle braiding machine using 50-80 dtex polylactic acid yarn as the braiding yarn and a polytetrafluoroethylene tube with a diameter of 2-4 mm as the core, and then the braided catheter is used as the core for secondary braiding; The core braided catheter was removed from the braiding machine, wrapped with aluminum foil, and heat-set at 145-160°C for 20-50 min to obtain a core polylactic acid braided double-layer catheter.

3. The preparation method according to claim 1, characterized in that: In the steps S2 and S5, the mass ratio of chitosan to gelatin is 3-4:1, and the mass ratio of chitosan to gelatin in S2 and S5 is the same.

4. The preparation method according to claim 1, characterized in that: In the steps S2 and S5, the mass ratio of chitosan to polyethylene glycol dipropylene oxide ether is 4-6:2, and the mass ratio of chitosan to polyethylene glycol dipropylene oxide ether in S2 and S5 is the same.

5. The preparation method according to any one of claims 1, characterized in that: In the steps S2 and S5, tea polyphenols account for 5-15% of the total mass of chitosan / gelatin / tea polyphenols, and the proportion of tea polyphenols in S2 and S5 is the same.

6. The preparation method according to claim 1, characterized in that: The neutralization and deacidification and cross-linking agent removal in step S6 include: Place the catheter in a 0.05-0.2 M Na2HPO4·12H2O solution and change the water every 20-30 min. After 2-3 h, wash the catheter with deionized water to remove the residual cross-linking agent; use a freeze dryer for secondary freeze drying.

7. The composite nerve conduit having an outer braided layer and an inner through-microchannel structure obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The composite nerve conduit comprises a double-layer braided outer conduit that has been subjected to multiple coating and cross-linking treatments, and the inner conduit is a hydrogel with a directional and arranged through-microchannel structure. The composite nerve conduit has excellent antibacterial and antioxidant properties.

Citation Information

Patent Citations

  • Bionic tissue engineering scaffold containing inner channel network and oriented pore structure as well as preparation method and application of bionic tissue engineering scaffold

    CN105311683A

  • Artificial nerve graft and preparation method

    CN111068118A